Population Aging and the Direction of Technical Change - Andreas Irmen (University of Heidelberg, Department of Economics, 2009)
An analytical framework is developed to study the repercussions between endogenous capital- and labor-saving technical change and population aging. Following an intuition often attributed to Hicks (1932), I ask whether and how population aging aff ects the relative scarcity of factors of production, relative factor prices, and the direction of induced technical change. Aging is equivalent to an increase in the old-age dependency ratio of an OLG-economy with two-period lived individuals. In this framework aging increases the relative scarcity of labor with respect to capital. Therefore, there will be more labor- and less capital-saving technical change. Unless there are contemporaneous knowledge spillovers across innovating firms technical change induced by a small increase in the old-age dependency ratio has no first-order effect on current GDP. The presence of capital-saving technical change is shown to imply that the economy's steady-state growth rate is independent of its age structure.
urn:nbn:de:bsz:16-opus-101722
Keywords: O41; O33; D92; D91; 330; Demographic Transition; Capital Accumulation; Direction of Technical Change; Alternde Bevölkerung; Technischer Fortschritt; Produktionsfaktor; Investition; Arbeit; Kapital; Theorie